Republic of Kazakhstan : 2008 Article IV Consultation; Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2008)
The Republic of Kazakhstan's 2008 Article IV Consultation shows that banks have lost access to new external financing, credit extension has stalled, and growth has slowed. Nevertheless, Kazakhstan has considerable public financial resources to help it weather the current situation and the country is benefiting from high oil and commodity prices. A realistic assessment of the health of banks needs to be made and steps taken to mitigate risks, including by bolstering capital bases, strengthening bank supervision, and further developing the financial safety net framework.